Radiological evaluation of pulmonary embolism: Advances in diagnostic accuracy and imaging techniques - Alahmad, Ahmed Ibrahim; Alanazi, Alaa Saud; Al-Falih, Tariq Abdulaziz (International journal of health sciences, 2020)
Background: Acute pulmonary embolism (PE) is a frequent, life-threatening condition predominantly caused by venous thromboembolism. Accurate and timely diagnosis is crucial for effective treatment, and imaging plays a central role in detecting PE. Recent advancements in imaging techniques have significantly improved diagnostic accuracy. Aim: This article reviews various radiological modalities for evaluating acute PE and their advances in diagnostic capabilities. Methods: The study examines the use of CT pulmonary angiography (CTPA), MRI, catheter pulmonary angiography, and other imaging techniques, such as echocardiography and nuclear medicine, highlighting their clinical applications and diagnostic precision. Results: CTPA is identified as the gold standard for diagnosing PE due to its high accuracy and speed, while MRI serves as a suitable alternative in patients with contraindications to iodinated contrast agents. Catheter angiography, though mostly replaced by CTPA, remains valuable for interventional treatments. Emerging techniques like dual-energy CT and non-contrast MRI show promise in enhancing diagnostic outcomes. Conclusion: Advances in imaging, including dual-energy CT and MRI, have improved diagnostic accuracy for PE, with each technique offering unique advantages. These innovations contribute to earlier detection, improved treatment planning, and better patient outcomes in acute PE management.